2001
DOI: 10.1523/jneurosci.21-10-03303.2001
|View full text |Cite
|
Sign up to set email alerts
|

p38 Activation Is Required Upstream of Potassium Current Enhancement and Caspase Cleavage in Thiol Oxidant-Induced Neuronal Apoptosis

Abstract: Oxidant-induced neuronal apoptosis has been shown to involve potassium and zinc dysregulation, energetic dysfunction, activation of stress-related kinases, and caspase cleavage. The temporal ordering and interdependence of these events was investigated in primary neuronal cultures exposed to the sulfhydryl oxidizing agent 2,2Ј-dithiodipyridine (DTDP), a compound that induces the intracellular release of zinc. We previously observed that tetraethylammonium (TEA), high extracellular potassium, or cysteine protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
198
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 153 publications
(213 citation statements)
references
References 58 publications
14
198
1
Order By: Relevance
“…12 These cells are rendered highly susceptible to dithiodipyridine (DTDP)-induced apoptosis following expression of Kv2.1, but not other potassium channels. 10 As in neuronal models, 3,4 we observed that Kv2.1-expressing CHO cells undergoing apoptosis have a similar surge in channel activity. Currents were measured with standard patch clamp electrodes after evoking them with a series of depolarizing membrane potential steps.…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…12 These cells are rendered highly susceptible to dithiodipyridine (DTDP)-induced apoptosis following expression of Kv2.1, but not other potassium channels. 10 As in neuronal models, 3,4 we observed that Kv2.1-expressing CHO cells undergoing apoptosis have a similar surge in channel activity. Currents were measured with standard patch clamp electrodes after evoking them with a series of depolarizing membrane potential steps.…”
Section: Resultsmentioning
confidence: 62%
“…27 This channel declustering appears to be correlated to calcium-dependent dephosphorylation of the channel and does not seem to affect surface expression. As the apoptotic current surge requires activation of the MAPK p38 pathway, 4 we believe that an initial phosphorylation event is responsible for the upregulation of Kv2.1 surface expression during apoptosis. Thus, it is unclear whether dispersion of surface clusters precedes or is related in any way to the apoptotic trafficking described in the present study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations